Neuroblastoma-derived hypoxic extracellular vesicles promote metastatic dissemination in a zebrafish model. - Anna Fietta; Pina Fusco; Giuseppe Germano; Sara Micheli; Marco Sorgato; Giovanni Lucchetta; Elisa Cimetta (PLoS ONE)
The zebrafish (Danio rerio) is a valuable model organism for studying human biology due to its easy genetic manipulation and small size. It is optically transparent and shares genetic similarities with humans, making it ideal for studying developmental processes, diseases, and drug screening via imaging-based approaches. Solid malignant tumors often contain hypoxic areas that stimulate the release of extracellular vesicles (EVs), lipid-bound structures released by cells into the extracellular space, that facilitate short- and long-range intercellular communication and metastatization. Here we investigate the effects of EVs derived from neuroblastoma (NB), a pediatric solid tumor, on metastatic niche formation using the zebrafish as an in vivo model. Intravascular injection in zebrafish embryos allows a non-invasive visualization of EVs dispersion, uptake, and interactions with host cells. To improve repeatability of our results and ease the injection steps, we used an agarose device replica molded from a custom designed micromilled aluminum mold. We first demonstrated that EVs released under hypoxic conditions promote angiogenesis and are more easily internalized by endothelial cells than those purified from normoxic cells. We also showed that injection of with hypoxic EVs increased macrophages mobilization. We then focused on the caudal hematopoietic tissue (CHT) region of the embryo as a potential metastatic site. After hypoxic EVs injection, we highlighted changes in the expression of mmp-9 and cxcl8b genes. Furthermore, we investigated the ability of NB-derived EVs to prime a metastatic niche by a two-step injection of EVs first, followed by NB cells. Interestingly, we found that embryos injected with hypoxic EVs had more proliferating NB cells than those injected with normoxic EVs. Our findings suggest that EVs released by hypoxic NB cells alter the behavior of recipient cells in the zebrafish embryo and promote metastatic outgrowth. In addition, we demonstrated the ability of the zebrafish embryo to be a suitable model for studying the interactions between EVs and recipient cells in the metastatic process.